1996
DOI: 10.1093/intimm/8.4.435
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni in IL-4-deficient mice

Abstract: Immunopathology and immune responses to Schistosoma mansoni were examined in IL-4 -/- mice. IL-5 and IL-10 production by lymphoid cells stimulated with soluble egg antigen (SEA), peripheral eosinophilia and serum levels of soluble IL-4 receptor but not IgE were all significantly elevated over background normal levels in IL-4 -/- mice as a result of infection. Additionally, IL-10 and IL-5 in addition to IL-2 and IFN-gamma transcripts were equally evident in diseased liver tissue from infected IL-4 -/- and wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
94
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 22 publications
14
94
1
Order By: Relevance
“…However, it is evident that IL-13 is the primary cytokine responsible for fibrosis. These data clarify the results reported for schistosome infections of STAT6-and IL-4R-deficient animals in which collagen deposition was found to be reduced (22,23) and IL-4-deficient animals in which collagen responses were normal (41). Because periportal fibrosis is a major cause of hepatic pathology in human schistosomiasis (42), regulation of IL-13 activity to limit collagen formation and deposition may have therapeutic implications.…”
Section: Discussionsupporting
confidence: 81%
“…However, it is evident that IL-13 is the primary cytokine responsible for fibrosis. These data clarify the results reported for schistosome infections of STAT6-and IL-4R-deficient animals in which collagen deposition was found to be reduced (22,23) and IL-4-deficient animals in which collagen responses were normal (41). Because periportal fibrosis is a major cause of hepatic pathology in human schistosomiasis (42), regulation of IL-13 activity to limit collagen formation and deposition may have therapeutic implications.…”
Section: Discussionsupporting
confidence: 81%
“…These results are in agreement with a report of increased sIL-4R production in Schistosoma mansoni-infected IL-4 knock-out mice [54]; and with a report by Blum et al [55] describing the existence of two different mechanisms for sIL-4R secretion: one that is IL-4-dependent and mediated by de novo synthesis from alternatively spliced sIL-4R-specific mRNA, and an IL-4-independent mechanism, putatively mediated through shedding of membrane IL-4R.…”
Section: Discussionsupporting
confidence: 94%
“…However, T cell responses were more generally affected in IL-4 ko mice (PedrasVasconcelos et al 2001). Metwali et al (1996) found granuloma size to be diminished in IL-4 ko mice but gave a different interpretation to cytokine patterns similar to those reported by Pearce et al (1996) and Chiramonte et al (1999b) found enlarged granulomas but decreased fibrosis in IL-4 ko mice. Other experiments in various strains of IL-4 ko mice have given discrepant results which we cannot yet interpret (Cheever et al 1998, Jankovic et al unpublished).…”
Section: The Role Of Cytokines In Granuloma Formation and Downregulatmentioning
confidence: 94%